Persepsi Auditor atas Konflik Kepentingan dan Perburuan Rente dalam Mendeteksi Indikasi Fraud - Natasha Priscilla Silooy; Novita Novita (Department of Accounting-Faculty of Economic and Business (FEB), 2021)
This study aims to prove that conflict of interest and rent seeking have a positive effect on indications of fraud based on the auditor’s perception. Indications of fraud in this study using the theory of fraud pentagon which consists of pressure, rationalization, opportunity, capability, and arrogance. Furthermore, conflicts of interest are seen from personal, relational, cultural, and structural indicators. While the indicators of rent seeking are seen from working capital, debt, corporate immunity, creative accounting, and corporate governance. This research is quantitative research using primary data. The population in this study are auditors who work in public accounting firms. The research sample consisted of 100 samples and was obtained using non-probability sampling and incidental sampling methods. The data analysis technique used the Partial Least Square method which consisted of descriptive and verification analysis. The results of the study show that conflicts of interest and rent seeking have a positive and significant effect on indications of fraud. The results of this study support the fraud pentagon theory that conflict-of-interest activities and rent seeking have an influence on indications of fraud.How to Cite: Silooy, N. P., & Novita. (2021). Persepsi Auditor atas Konflik Kepentingan dan Perburuan Rente dalam Mendeteksi Indikasi Fraud. Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 255-268.